1995
DOI: 10.1007/bf01181605
|View full text |Cite
|
Sign up to set email alerts
|

The oligodendroglial reaction to brain stab wounds: An immunohistochemical study

Abstract: Myelin/oligodendrocyte specific protein was compared to glial fibrillary acidic protein and 2'3'-cyclic nucleotide 3'-phosphodiesterase expression in normal rat brains and following stab wounds to the cerebral cortex, corpus callosum and hippocampus. Animals with stab wounds were allowed to recover for 5, 15, 28, 45 and 70 days post-operation before fixation by perfusion. Sections were reacted with antibodies against myelin/oligodendrocyte specific protein, glial fibrillary acidic protein and 2'3'-cyclic nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…The post-injury reaction of oligodendrocytes is poorly understood. Proliferation of oligodendrocytes has been shown following stab wound lesion in the brain, indicating that they might undergo an attempt for repair (Ludwin, 1984(Ludwin, , 1985Xie et al, 1995). However, it is not known whether this proliferative response takes place also in other CNS compartments (e.g., the spinal cord) or whether it actually leads to increased myelin synthesis.…”
Section: Introductionmentioning
confidence: 95%
“…The post-injury reaction of oligodendrocytes is poorly understood. Proliferation of oligodendrocytes has been shown following stab wound lesion in the brain, indicating that they might undergo an attempt for repair (Ludwin, 1984(Ludwin, , 1985Xie et al, 1995). However, it is not known whether this proliferative response takes place also in other CNS compartments (e.g., the spinal cord) or whether it actually leads to increased myelin synthesis.…”
Section: Introductionmentioning
confidence: 95%
“…Although oligodendrocytes can respond to damage and proliferate in the brain following trauma [7,23] , and transplantation of 0-2A progenitor cells [28] or cultured oligodendrocytes [29] can repair demyelinating damage in the brain, the role of oligodendrocytes in the repair process after brain injury such as trauma and ischemia has not been fully investigated. Mandai et al [8] demonstrated accumulation of oligodendrocytes in the ischemia-induced brain lesion with in situ hybridization histochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Ludwin and Sternberger [22] found that oligodendrocytes incorporated tritiated thymidine following cuprizone-induced demyelination. Xie et al [7] , after brain stab wounds, found that the number of reactive oligodendrocytes along the wound track increased until 28 days after operation, and then decreased so that very few were found at 70 days after operation. In contrast, the number of GFAP-positive cells continued to increase throughout the time period's studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations